The effects on growth, oxidative stress, Vitamin A, E, C and Beta Caroten of Vitamin E and C added to the ration of freshwater crayfish (Astacus leptodactylus, Esch. 1823) in Moulting Period - Barim-Öz, Özden; Karatepe, Mustafa (Ataturk Universitesi, 2016)
In this study, it was examined the effects of dietary antioxidant (Vitamin E (VE), Vitamin C (VC)) which supplemented on crayfish Astacus Leptodactylus diets during moulting on survival rate, live weight gain, specific growth rate, oxidative stress in hepatopancreas, muscle and gills tissues (malondialdehyde (MDA)), vitamins A, E, C, amount of ?-carotene and astaxanthin. For this aim, a control diet (K) containing 38% crude protein was prepared. Crayfish of the experimental E (DE), experimental C (DC) and experimental DC (DEC) groups were respectively fed by adding the 150 mg kg-1 Vitamin E, 200 mg kg-1 Vitamin C and 150 mg kg-1 and Vitamin E /200 mg kg-1 Vitamin C in this ration. At the end of the study, it was determined that the supplemental of antioxidants in the diet decreased MDA levels in the tissues during moult, but it wasn't effected on the growth. It was assigned that the levels of Vitamin E, C, A, beta-carotene, and astaxanthin were high in the tissues of crayfish in the DE, DC and DEC groups according to C group. It was determined that the addition of 150 mg kg-1 Vitamin E to the diet during moulting is beneficial. Additionally, the meat quality of abdominal muscles of crayfish which consumed by people was also found to be reduced in a considerable amount during molting.
Kabuk De?iştirme Döneminde Kerevit (Astacus leptodactylus, Esch. 1823) Yemine Ilave Edilen Vitamin E ve C'nin Büyüme, Oksidatif Stres, Vitamin A, E, C ve Beta Karoten Üzerine Etkileri
Keywords: Astacus leptodactylus; Carotenoid; MDA; Vitamin